Applications of Lasers in Pediatric Dentistry and Their Types (International Journal of Food and Nutritional Sciences, 2022)
Drilling has recently been replaced with laser technology in the realm of dentistry. Using cutting-edge tools like lasers to create a less painful first dental experience can be a successful preventive and therapeutic approach in paediatric dentistry. The new, less intrusive technology must be learned by pedodontists and incorporated into everyday practise. This study aims to review the various laser types that are now available and their uses in paediatric dentistry. To locate pertinent publications published between 2000 and 2014, an electronic search was conducted in the databases of IranMedex, InterScience, Scopus, Science Direct, PubMed, ProQuest, Medline, and Google Scholar. Additionally, pertinent textbooks were reviewed. Many common diagnostic and therapeutic dental treatments can be effectively replaced using laser technology. It works particularly well for pulp therapy, caries detection and removal, minimising the risk of infection, inflammation, and swelling, and bleeding. On the other hand, youngsters tolerate laser treatment well because it causes less intrusion. Parental, dental, and child satisfaction all increase as a result of better patient compliance.